Clickers and Online Homework in the Criminal Justice Classroom: A Test Study. Issue 3 (3rd July 2019) - Cass, Amy I.
Abstract: The criminal justice discipline has few studies that explore the use of technology as a supplement to traditional face-to-face instruction. Using a sample of criminal justice students enrolled in two sections of the same 300-level foundational criminal justice course, this study examines the impact of clickers and online homework on student performance in the course, as well as observes student perceptions of the integrated technology. Results reveal that while students perceived the technologies as helpful to their learning, the addition of technologies to the one section of the course had little impact on student performance indicators such as test scores and final letter grades. Potential explanations for these findings and directions for future research are discussed; and suggestions on how to potentially make these supplemental tools more useful are provided.